Fluid overpressurization of rock fractures: experimental investigation and analytical modeling - Ji, Yinlin (2022)
Fluid-induced seismicity in tectonically inactive regions has been attributed to fluid overpressurization of rock fractures during natural resource extraction and storage. We conducted a series of triaxial shear-flow experiments on sawcut fractures in granite and showed that the fracture responses can be dissimilar under various fluid pressurization conditions. For pressure-controlled fluid pressurization, a uniform fluid pressure distribution can be promoted by lowering pressurization rate and enhancing fracture permeability. However, during volume-controlled fluid pressurization, a high pressurization rate causes a drastic increase in fluid pressure before fracture failure. In this case, our analytical model reveals that the fracture area and normal stiffness also influence fluid pressure variations. The maximum seismic moment predicted by this model is well validated by the experimental data for the cases with low pressurization rates. The discrepancy between the analytical and experimental data increases with higher fluid overpressure ratio owing to the assumption of uniform fluid pressure distribution in the model. The sensitivity analysis demonstrates the importance of fracture size estimation in the maximum seismic moment prediction. Our model can potentially be applied to control the fluid overpressurization of rock fractures and to mitigate the risks of fluid-induced seismicity.